Efeito antrópico na diversidade de Maruins (Diptera: Ceratopogonidae) em uma área de assentamento rural na Amazônia - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
The biting midges Culicoides are vectors of some etiological agents to humans and other mammals. There are just a few studies in Amazon basin about that insects and the diversity and richness of this genus is underestimated. The aims of this study were to describe the fauna of midges in a rural settlement in Amazon and to understand how the anthropic effects may affect the richness and abundance of these putative local vectors. Collections were done by CDC light traps in some environment as primary forest, forest borders, secondary forest, fruit garden and peridomiciliary area with animal shelters. We identified 6.093 individuals, distributed in 42 species, 39 morphotypes of seven subgenera and /or species groups and five new species of Reticulatus group. We found 13 new occurrence to Amazonas State C. aldomani, C. batesi, C. brownie, C. debilipalpis, C. flavivenula , C. franklini, C. glabellus, C. guamai, C. guttatus, C. ocumarensi, C. paramaruim, C. pusilloides and C. tidwelli, and two new occourence to the country, the species C. brownie and C. tidwelli. Our results show that different anthropic levels affect the abundance and diversity of midges. The diversity was high in less anthropized environments. The peridomiciliary areas had a high richness and abundance of Culicoides.
Keywords: Insetos transmissores de patologia - Amazônia; Agentes patogênicos - Amazônia; Culicoides - Diversidade - Amazônia; Diptera Ceratopogonidae; Diversidade de Maruins - Efeito antrópico; CIÊNCIAS DA SAÚDE